Reaching out to the underprivileged children: a charity concert platform to raise funds - Adnan, Afni Anida; Vijayarajoo, Angeline Ranjethamoney; Saleh, Noor Shahariah; Azmi, Sharina Salmi; Syed Ahmad, Tuan Sarifah Aini (Universiti Teknologi MARA, Kedah, 2024)
Corporate Social responsibilities in Universities, also known as University Social Responsibilty (Meseguer-Sanchez, 2023) has become a requirement of Higher Education Institutions (HEI), to produce a positive impact on society. With this in mind, The Academy of Language Studies of Universiti Teknologi MARA has decided to embark on a project with two phases involved – (1) fundraising and (2) visits to two orphanages in the city of Seremban. The two objectives of the CSR project by APB Seremban address two different target groups: One to fulfill the needs of the less privileged children and the other, to enhance the awareness and appreciation for music by the group of people in more privileged spaces. A group of researchers from the Academy of Language Studies, UiTM Seremban, identified two orphanages in Seremban where the need was for books, toys and spending time reading with the children. The methodology comprises a questionnaire to the participants before the concert regarding their awareness of the objectives of the charity and their awareness of semi classical and pop music. Towards the end of the concert, a similar post questionnaire will be distributed. The major results expected are the awareness of the community to reach out to children in need by donating their money and time towards the education of the less privileged children as well as an enhanced appreciation and greater frequency for musical concerts – classical -pop. A subsequent analysis will be carried out to identify the outcomes of this programme for the children through repeated visits to their orphanages and the conducting of various pedagogic activities.